THE STRATEGIES OF ENGLISH LECTURERS IN TEACHING SPEAKING - Marmoah, Sri (Journal of Research in English Language Teaching, 2017)
One of the responsibilities a lecturer should concern while teaching the students is to create a communicative environment, instead of worrying about the process of teaching and put no regard on the studentsâ language ability. This research aimed to find out the kinds of strategy in teaching speaking of English Education Study Program and to know the application of those strategies in the classroom. The research designed in this study was a descriptive qualitative to describe the status of things in the present or in the past. It meant that the data gathered were not analysed in term of number statistical accounting, but were analysed in the qualitative form which is more than more numbers or frequencies. Based on the research findings, it can be concluded that the most lecturersâ teaching strategy that used in teaching speaking are using recording & transcripts, dialogues, discussion, classroom conversation, and casual chat. Lecturersâ used that technique because it is based on the handbook and it is easy to practice. Some other strategy sometimes used by lecturersâ, but the frequency is very rare. The most used are dialogues and conversation and chat and jokes. Based on the discussion, most students like the strategy that used by the teacher. They followed lecturersâ instruction. Â  Keywords: lecturersâ strategy, teaching speaking